Efficient knockin mouse generation by ssDNA oligonucleotides and zinc-finger nuclease assisted homologous recombination in zygotes. - Bin Shen; Xin Zhang; Yinan Du; Jianying Wang; Jun Gong; Xiaodong Zhang; Peri H Tate; Hongliang Li; Xingxu Huang; Wensheng Zhang (PLoS ONE, 2013)
The generation of specific mutant animal models is critical for functional analysis of human genes. The conventional gene targeting approach in embryonic stem cells (ESCs) by homologous recombination is however laborious, slow, expensive, and limited to species with functional ESCs. It is therefore a long-sought goal to develop an efficient and simple alternative gene targeting strategy. Here we demonstrate that, by combining an efficient ZFN pair and ssODN, a restriction site and a loxP site were successfully introduced into a specific genomic locus. A targeting efficiency up to 22.22% was achieved by coinciding the insertion site and the ZFN cleavage site isogenic and keeping the length of the homology arms equal and isogenic to the endogenous target locus. Furthermore, we determine that ZFN and ssODN-assisted HR is ssODN homology arm length dependent. We further show that mutant alleles generated by ZFN and ssODN-assisted HR can be transmitted through the germline successfully. This study establishes an efficient gene targeting strategy by ZFN and ssODN-assisted HR in mouse zygotes, and provides a potential avenue for genome engineering in animal species without functional ES cell lines.